An Investigation on the Business Strategies and Key Success Factors of Financial Holding Companies in Taiwan - Lin, chingpei (2007)
In order to pursue omni-directional developing, reducing the operating cost and expanding market channel, financial holding companies (FHCs) seek the way to enlarge operational scale and to merge other financial institutions. Consequently, FHCs expect to occupy a tiny space in the holding domain of finance with keen competition. It is the most important subject on the management tactics of financial holding companies, as the financial domain is reformed, how does the financial holding company set their own competition advantage to integrate the whole source effectively, develop the new products and set up one's own key competitiveness progressively.